1994
DOI: 10.2307/249521
|View full text |Cite
|
Sign up to set email alerts
|

Alignment of the IS Functions with the Enterprise: Toward a Model of Antecedents

Abstract: Identifying the best way to organize the IS functions within an interprise has been a critical IS management issue since the mid-1980s. Yet to date, MIS researchers have offered little empirical evidence on which to base guidelines for the practitioner. This study seeks to explain a firm's IS organization design decision for a decentralized, centralized, or "hybrid" locus of responsibility from an expanded set of environmental overall organizational, and IS-specific antecedents as well as a larger concept of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
246
0
8

Year Published

1997
1997
2015
2015

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 359 publications
(255 citation statements)
references
References 47 publications
1
246
0
8
Order By: Relevance
“…These arrangements need to be aligned with factors such as the host organization characteristics, technology assimilation, the strategic impact of IT, and the IT heritage. Brown and Magill (1994) suggested a simpler structural typology involving IT structures that are centralized, decentralized, or hybrid. They provided evidence that each structure can be effective, given the right circumstances.…”
Section: Structural Dimensionsmentioning
confidence: 99%
See 1 more Smart Citation
“…These arrangements need to be aligned with factors such as the host organization characteristics, technology assimilation, the strategic impact of IT, and the IT heritage. Brown and Magill (1994) suggested a simpler structural typology involving IT structures that are centralized, decentralized, or hybrid. They provided evidence that each structure can be effective, given the right circumstances.…”
Section: Structural Dimensionsmentioning
confidence: 99%
“…In another study, Chan et al (2006) examined antecedents to alignment directly under the control of IT management (such as shared domain knowledge, planning sophistication, and the credibility of the IT group due to prior IT success), and factors external to the IT group such as organizational size and environmental uncertainty. In earlier research, Brown and Magill (1994) identified antecedents such as corporate vision, strategic IT role, satisfaction with management of technology, satisfaction with the use of technology, and the locus of control for system approvals.…”
Section: Antecedents To Alignmentmentioning
confidence: 99%
“…Firms with such IS contexts are likely to be firms with highly autonomous business units (Earl 1989) that compete in unrelated businesses (Brown and Magill 1994), and thus have significantly lower opportunities for IT-related cross-unit synergies (Brown and Magill 1998). A corporate level coordination role may not even exist in such firms, and horizontal coordination initiatives may even be voluntary (DeSanctis and Jackson 1994).2…”
Section: Federal (Hybrid)mentioning
confidence: 99%
“…[Zentralisierung der IT] Eine zentrale Position der IT-Governance-Literatur zeigt eine Verbindung der Unsicherheit der Umweltbedingungen zur Dezentralisierung der ITGovernance: Steigender Unsicherheit kann mit einer dezentralen IT begegnet werden, um Planungsabweichungen lokal aufzufangen [s. Brown/Magill 1994;Brown 1997]. Das Projekt bietet auf Grund der reduzierten Organisationsgröße intern nicht die Möglichkeit, IT dezentral zu verteilen -keines der untersuchten Beispiele zeigte derartige Tendenzen und insbesondere auch nicht Projekte, die mehrere geographisch verteilte Produktionsstandorte verbanden [NOS, BOS].…”
Section: It-bezug Des Gesamtprojektsunclassified